Development of stability-indicating lc method assisted by design of experiment for fenticonazole cream analysis in presence of degradation product - Silva, Thais Araújo [UNESP]; Côrrea, Josilene Chaves Ruela [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2019)
Fenticonazole is an antifungal drug widely used in a cream formulation including as a generic medicine. Stability studies of fenticonazole in a cream formulation are very scarce. In this research, we intent to contribute to generic medicines quality control and provide reliable data seeking for insertion of fenticonazole monograph in official compendia. Therefore, in this work it was studied the behavior of fenticonazole under several conditions and developed a stability-indicating LC method to separate the degradation products and quantify the drug in presence of them. It was used the Design of Experiments (DoE) as tool to achieve robust and easy transferable method. Fenticonazole stability was evaluated under aqueous, alkaline (0.1 M NaOH), acidic (0.1 M HCL) and oxidative (3% v/v, H2 O2 ) at ambient temperature and heating at 90°C, over 6 hours. The drug shows to be unstable under all stressed test conditions. It was completely degraded under acid medium with arising of degradation products. The robust and stability indicating LC method was validated. It is able to reveal the fenticonazole instability and to separate its degradation product with accuracy and precision (RSD ˂ 2%) and without any placebo interferences.
Dsenvolvimento de método cromatográfico (Lc) indicativo de estabilidade empregando planejamento experimental para análise de fenticonazole creme na presença de produtos de degradação
Keywords: Degradation Product; Design of Experiment; Drug Stability; Fenticonazole; Liquid Chromatogtaphy; Quality Control